Sanguina nivaloides and Sanguina aurantia gen. et spp. nov. (Chlorophyta): the taxonomy, phylogeny, biogeography and ecology of two newly recognised algae causing red and orange snow - Procházková, Lenka (FEMS Microbiol Ecol, 2019)
Melting snowfields in polar and alpine regions often exhibit a red and orange colouration caused by microalgae. The diversity of these organisms is still poorly understood. We applied a polyphasic approach using three molecular markers and light and electron microscopy to investigate spherical cysts sampled from alpine mountains in Europe, North America and South America as well as from both polar regions. Molecular analyses revealed the presence of a single independent lineage within the Chlamydomonadales. The genus Sanguina is described, with Sanguina nivaloides as its type. It is distinguishable from other red cysts forming alga by the number of cell wall layers, cell size, cell surface morphology and habitat preference. Sanguina nivaloides is a diverse species containing a total of 18 haplotypes according to nuclear ribosomal DNA internal transcribed spacer 2, with low nucleotide divergence (≤3.5%). Based on molecular data we demonstrate that it has a cosmopolitan distribution with an absence of geographical structuring, indicating an effective dispersal strategy with the cysts being transported all around the globe, including trans-equatorially. Additionally, Sanguina aurantia is described, with small spherical orange cysts often clustered by means of mucilaginous sheaths, and causing orange blooms in snow in subarctic and Arctic regions.